Cornelius Marius Schoonmaker papers - Schoonmaker, Cornelius Marius, 1839-1889.
Correspondence, letterbook, order book, printed material, scrapbooks, and an unpublished biography detailing Schoonmaker's naval career. Includes Schoonmaker's letters regarding China and the Far East (East Asia), a letter concerning the survivors of the ship Polaris, accounts of the battle of Mobile Bay, Ala., and details of Schoonmaker's drowning in a hurricane which also wrecked his ship, the screw sloop Vandalia. Correspondents include William E. Chandler, John Adolphus Bernard Dahlgren, Thomas A. Dornin, David Glasgow Farragut, Louis Malesherbes Goldsborough, John C. Howell, George M. Robeson, Richard W. Thompson, Isaac Toucey, Gideon Welles, and William C. Whitney.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Chandler, William E. -- 1835-1917 -- Correspondence; Dahlgren, John Adolphus Bernard, -- 1809-1870 -- Correspondence; Dornin, Thomas A. -- 1800-1874 -- Correspondence; Farragut, David Glasgow, -- 1801-1870 -- Correspondence; Goldsborough, Louis Malesherbes, -- 1805-1877 -- Correspondence; Howell, John C. -- Correspondence; Robeson, George M. -- 1829-1897 -- Correspondence; Thompson, Richard W. -- 1809-1900 -- Correspondence; Toucey, Isaac, -- 1796-1869 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; Whitney, William C. -- 1841-1904 -- Correspondence; Polaris (Ship); Vandalia (Screw sloop); Mobile Bay, Battle of, Ala., 1864.; Alabama -- History -- Civil War, 1861-1865.; China -- Description and travel; East Asia -- Description and travel; United States -- History -- Civil War, 1861-1865 -- Campaigns; Naval officers